Mesenchymal Stem Cells in Treatment of Spinal Cord Injury and Amyotrophic Lateral Sclerosis - Sykova, Eva; Cizkova, Dasa; Kubinova, Sarka (Frontiers in Cell and Developmental Biology, 2021)
Preclinical and clinical studies with various stem cells, their secretomes and extracellular vesicles indicate their use as a promising strategy for treatment of various diseases and tissue defects including neurodegenerative diseases such as spinal cord injury (SCI) and amyotrophic lateral sclerosis (ALS). Autologous and allogenic mesenchymal stem cells (MSCs) are so far the best candidates for use in regenerative medicine. Here we review the effects of implantation of MSCs (progenitors of mesodermal origin) in animal models of SCI and ALS and in clinical studies. MSCs possess multilineage differentiation potential and are easily expandable in vitro. These cells, obtained from bone marrow, adipose tissue, Wharton jelly or even other tissues, have immunomodulatory and paracrine potential, release numbers of cytokines and factors which inhibit proliferation of T cells, B cells and natural killer cells, and affect dendritic cell activity. They are hypoimmunogenic, migrate towards lesion sites, induce better regeneration, preserve PNNs and stimulate neural plasticity. There is wide use of MSCs systemic application or MSCs seeded on scaffolds and tissue bridges made from various synthetic and natural biomaterials, including human decellularized ECM or nanofibers. Positive effects of MSCs implantation have been recorded in animals with SCI lesions and ALS. Moreover, promising effects of autologous as well as allogenic MSCs for treatment of SCI and ALS was demonstrated in recent clinical studies.